The Role of Meja Panjang Cultural Tourism in Improving the Community’s Economy: A Case Study in Merasa Village - Rosid, Tamam (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
Tourism is one of the important elements in increasing regional income and economic growth, and it is also expected to have an impact on improving the welfare of the community. The government revitalized the a Dayak Cultural Attraction to manage cultural tourism in Berau City. The museum management carries out various events and promotional activities to increase the number of tourist visits from within and outside the city. It is expected to provide benefits to the increase in local revenue, employment opportunities, and the welfare of the community. This study aims to determine and explain the effect of promotion and tourist visits on the welfare of the community around the Meja panjang Dayak Cultural Attraction . This study uses primary data and multiple linear regression analysis methods. The results showed that there was a partial relationship between the variables of tourist spot promotion and tourist visits to community welfare but did not have a significant nature. While the variable promotion of tourist attractions and tourist visits together (simultaneously) has a positive relationship. This is evidenced by the increase in tourist attraction promotion indicators and the increase in tourist visits to Meja Panjang Cultural attractions, which can positively impact community welfare.